(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the features of preparing students in the vocational education system for independent family life based on national values. The study highlights the importance of strengthening the institution of family, reducing the divorce rate, and developing spiritual and moral education. The role of community programs, legal frameworks, and educational strategies in equipping young people with the necessary skills for responsible family life is analyzed. The research results indicate that practical training and cooperation among stakeholders play a crucial role in enhancing the effectiveness of family life preparation programs.